A short solid-state synthesis leading to titanate compounds with porous structure and nanosheet morphology - Kőrösi László Tamás; Papp Szilvia; Csapó Edit; Meynen Vera; Cool Pegie; Dékány Imre (2012)
A novel method was developed for the synthesis of titanate nanosheets with high surface area. A solid-state mixture of NaOH and TiO(2) was reacted at 600 degrees C for several minutes. The aqueous dispersion of the resulting melt was aged at room temperature for periods up to 14 days. After hydrochloric acid treatment and washing procedures, the reaction product was characterized by X-ray diffraction, Raman spectroscopy, N(2)-sorption and small-angle X-ray scattering measurements. The titanate compound not subjected to the aging process was amorphous and possessed a microporous framework, while the aged samples displayed nanosheet morphology and high specific surface area (396-509 m(2) g(-1)). It was revealed that the very short heat treatment is of crucial importance for the titania-titanate phase transformation, while the aging process is needed for the morphological evolution of the titanate samples. The effects of the aging time on the structure and the morphology are discussed. (C) 2011 Elsevier Inc. All rights reserved.